2015
DOI: 10.1007/s40011-015-0544-7
|View full text |Cite
|
Sign up to set email alerts
|

Relative Efficiency of Zinc Sulphate and Chelated Zinc on Zinc Biofortification of Rice Grains and Zinc Use-Efficiency in Basmati Rice

Abstract: Zinc deficiency in human nutrition is widespread in developing Asian and African countries where cereal grains are the staple food. Agronomic biofortification of Zn is a new innovative approach to get rid of Zn malnutrition from the poorest of the poor rural masses, who will never have money to buy mineral supplements nor can afford to improve the components of their diet by incorporating animal products. Hence, a field experiment was conducted during 2010 and 2011 on a sandy clay-loam soil (typic Ustochrept) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…The similarity of soluble Zn sources and chelates in nutrition and maize production was also observed in another grass, the rice that is demanding in the micronutrient as indicated by Shivay et al (2016).…”
Section: Experiments IIImentioning
confidence: 64%
See 1 more Smart Citation
“…The similarity of soluble Zn sources and chelates in nutrition and maize production was also observed in another grass, the rice that is demanding in the micronutrient as indicated by Shivay et al (2016).…”
Section: Experiments IIImentioning
confidence: 64%
“…Despite the differences between the salts and chelates, studies show that these can present similar agronomic efficiencies in different cultures' growth and production (McBeath and McLaughlin 2014;Shivay et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Reports indicate that the 1000-grain weight was not affected by different concentrations of silicon (Yazdpour et al, 2014a), which is consistent with the results of the present research. In contrast, a piece of research showed that the zinc application from different sources had a significant effect on thousand grain weight of rice (Shivay et al, 2016).…”
Section: Discussionmentioning
confidence: 91%
“…All Zn treatments for agronomic biofortification of Zn in corn grain as well as in stover were in the following order: 5 kg soil + 1 kg foliar ˃ 1 kg foliar ˃ 2.83 kg as Zn-coated urea to soil ˃ 5 kg soil. Shivay et al, (2015) reported that soil application of ZnSHH or Zn-EDTA significantly increased the Zn concentration in grain of rice crop over NPK fertilization, which were at par with two or three applications of 0.2% solutions of ZnSHH or Zn-EDTA or one or two applications of 0.5% solutions of ZnSHH or Zn-EDTA.…”
Section: Agronomic Biofortificationmentioning
confidence: 99%